A new genus and species of Orphninae (Coleoptera: Scarabaeidae) associated with epiphytes in an Andean cloud forest in Ecuador - Frolov, Andrey V.; Vaz-De-Mello, Fernando Z. (Zootaxa, 2015)
Orphninae (Coleoptera: Scarabaeidae) are represented in the New World by the tribe Aegidiini, which is comprised of four genera (Paulian 1984). Examination of material collected in Ecuador revealed a series of the Aegidiini specimens from an undescribed species that cannot be classified as a member of one of the known genera. The new species is herein described and a new genus is established. Apart from the distinctive morphological characters, the new taxon shows an unusual, for the Orphninae, association with canopy epiphytes.